Integrating Historical Knowledge with Modern Strategies: Addressing Malaria in the Context of Climate Change and Medical Diplomacy in Northern Nigeria, 1940 to 2020 - Itodo, Unekwu Friday (African historical review, 2025)
Climate change is significantly impacting the spread of vector-borne diseases like malaria in Lokoja in the twenty-first century faced with interconnected global crises. Altered temperature and rainfall patterns disrupt ecosystems, affecting disease vectors' distribution, populations, and life cycles. This directly expands the geographic range of vector-borne diseases, introducing them to new areas. This study examined this issue through the lens of social vulnerability theory, which explores how social factors influence people's susceptibility to environmental hazards. The focus is on Northern Nigeria, a region with high malaria prevalence rates. Qualitative methods like interviews, focus groups, and document analysis were used to explore challenges in malaria control. The findings revealed several challenges: low malaria awareness, limited healthcare access, cultural barriers to prevention, and insufficient funding. These findings highlight the importance of incorporating climate change considerations into global health initiatives, especially when addressing vector-borne diseases in vulnerable populations. The study suggests that increased education, improved access to healthcare, culturally sensitive control measures, solving climate change challenges, and the use of medical diplomacy, which offers crucial pathways, will be essential for funding and promoting joint research for innovative tools and strategies.